Pulping Studies of Hill Jati Bamboo (Bambusa tulda) from Cachar Hills - Bhola, P. P. (Indian Forester, 1976)
Proximate chemical analysis and fibre dimensions of Hill Jati Bamboo growing in Cachar Hills (Bambusa tulda) are given. Pulping and bleaching studies of this species are also recorded. It is observed that under the conditions studied, this species of bamboo is suitable for manufacture of wrapping, writing and printing papers.